Facets of Consumer Behavior Management: Reflexes and Neurointerface (Global Journal of Management and Business Research, 2023)
The Internet, social networks, cloud services and e-commerce have rapidly become important components of modern human life. However, recent studies of neurotechnological companies have marked the foreseeable transition of civilization from the stage of information development to cyber-physical systems that combine the real "analog" world and cyberspace. The scientific novelty and purpose of this study is due to the lack of a holistic study of the evolution of the theory of behavioral design in world science. The interdisciplinary approach is the main method of research, on the basis of which the integration of data, tools, techniques, concepts of physiology, psychology, neurobiology, addictology, sociology, computer science, cybernetics, captology, political science, economics, ethics is carried out. The concept of behavioral design has emerged and is developing as a synthesis of the ideas of the physiological theory of reflexes and reinforcement, the psychoanalytic theory of crowds and operational conditioning, theories of public opinion management and organizational change, institutional concepts of consumer behavior, computerization and development of data networks, neurobiology and artificial intelligence. In foreign practice, behavioral design is used in digital devices, architecture, in the processes of reducing crime, protecting against errors in the organization of processes in healthcare, creating energy-saving, resource-saving and ecofriendly products, solving problems with coronavirus, reducing unproductive screen time, creating virtual products for healthcare, education, social security.
Keywords: behavioral design; neurointerface; cyberphysical systems; addictive design; captology; digital goods; neuroethics